European Integration - a Comparative Perspective Between Romania and the Republic of Moldova - Claudia Bobalca; Camelia Soponaru; Oana Ciobanu (CES Working Papers, 2013)
The integration in the European Union is a reality for some countries and a purpose for others. This process generates a lot of benefits for an EU member but also involves important costs. The research investigates the opinion of two different people (Romanian and Moldavian) about the perceived effects of EU integration. The results show that Moldavians are more interested in European Union then Romanians. For Moldavians, the independent economy is considered to be the greatest advantage of their country not being integrated in UE. The perceived disadvantages are the lack of free movement, corruption and low level of general development. For Romanians, the most important perceived advantage for integration in EU is free movement. The biggest disadvantage is that foreign sellers have more benefits then local sellers.
Keywords: F0; F60; 330; EU integrations; Romania; Republic of Moldova Romania